KNOWLEDGE OF MAINTENANCE INTRAVENOUS FLUID THERAPY IN ACUTELY ILL HOSPITALIZED CHILDREN AMONG RESIDENTS - Haque, Anwarul; Mirza, Sadiq; Jafri, Sidra Kaleem; Naseem, Faizia; Khan, Khalid Mahmood; Afzal, Muhammad Faheem; Hamid, Muhammad Haroon (Journal of Ayub Medical College Abbottabad, 2016)
Background: Isotonic saline is recommended as maintenance intravenous fluid therapy (MIVFT) for most of the acutely ill hospitalized children. The aim of this study is to assess the current knowledge of paediatric residents regarding the selection of MIVFT in hospitalized children. Methods: We conducted a paper-based questionnaire survey to paediatric residents from ten centres asking selection of MIVFT in four common clinical scenarios in 6-month and 10-year old patients as well as monitoring of fluid balance and electrolyte. Results: 445 responses were collected (>90% response rate). Majority [78.3% (n=348)] of them were FCPS-trainees. The 0.9%, 0.45% and 0.2% solution were selected by 45.8%, 43.98% and 10.92% respectively. The isotonic and hypotonic solution was prescribed in 6-mo (35.22% vs. 64.76% [p<0.001]) and 10-year (54.49% vs. 44.98%) in four different clinical scenarios respectively. 0.45% solution was most commonly prescribed MIVFT in pneumonia (50.22%) and meningitis (45.39%) and 0.9% solution was most commonly selected in acute gastroenteritis (55.05%) and post-operative patients (51.23%). Fluid balance and electrolyte monitoring were selected by 96.9% and 55.7% respondents respectively. Conclusion: Our survey reports that more than fifty percent of paediatric residents have inadequate knowledge about maintenance intravenous fluid therapy in acutely ill hospitalized children. Keywords: Children, maintenance intravenous fluid, knowledge, residents